2019
DOI: 10.1111/desc.12840
|View full text |Cite
|
Sign up to set email alerts
|

Children can optimally integrate multisensory information after a short action‐like mini game training

Abstract: Combining information across different sensory modalities is of critical importancefor the animal's survival and a core feature of human's everyday life. In adulthood, sensory information is often integrated in a statistically optimal fashion, so that the combined estimates of two or more senses are more reliable than the best single one.Several studies have shown that young children use one sense to calibrate the others, which results in unisensory dominance and undermines their optimal multisensory integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Along with a self-report, we also measured the recalibration of finger position, hypothesising that if the illusion also contributes to more implicit characteristics of body perception (i.e., the body schema), participants would recalibrate their finger position sense upwards with respect to the real position of their finger. In particular, given the impaired multisensory integration processes in children documented in other studies [30][31][32] we expected two possible outcomes: on the one hand, if children tend not to integrate audio-haptic information, this will reflect on the mechanisms underlying the illusion, thus preventing them from perceiving the illusion; on the other hand though, studies have shown that children up to 6 years of age present an auditory dominance 43 , and this may reflect on this illusion too, thus promoting perception of the illusion.…”
mentioning
confidence: 99%
“…Along with a self-report, we also measured the recalibration of finger position, hypothesising that if the illusion also contributes to more implicit characteristics of body perception (i.e., the body schema), participants would recalibrate their finger position sense upwards with respect to the real position of their finger. In particular, given the impaired multisensory integration processes in children documented in other studies [30][31][32] we expected two possible outcomes: on the one hand, if children tend not to integrate audio-haptic information, this will reflect on the mechanisms underlying the illusion, thus preventing them from perceiving the illusion; on the other hand though, studies have shown that children up to 6 years of age present an auditory dominance 43 , and this may reflect on this illusion too, thus promoting perception of the illusion.…”
mentioning
confidence: 99%
“…Del mismo modo sucede para entender las intenciones de los demás en contextos comunicativos. El juego sería el principal medio para el desarrollo del niño, ya que se considera su medio de comunicación predominante, sirviendo para vincular intenciones y acciones con el significado de los objetos y situaciones (Rodríguez, 2009) Es por ello que los niños jugando comienzan a comprender los signos intencionales en contextos comunicativos, precisamente por el vínculo con los objetos a los que se refieren estos signos (Nava, Föcker, & Gori, 2020).…”
Section: Etapa Perlocutivaunclassified
“…The developmental time course of the ability to integrate multisensory cues is still under debate. In some studies, only children older than 8 years were found to integrate sensory cues in a Bayes optimal fashion (Dekker et al, 2015;Gori et al, 2008;Nardini et al, 2008Nardini et al, , 2010Nardini et al, , 2013Petrini et al, 2014;Scheller et al, 2021), whereas in other studies, younger children also appeared to be able to integrate, potentially as a result of differences in task and feedback (Negen et al, 2019;Rohlf et al, 2020), or due to training (Nava et al, 2020).…”
Section: Introductionmentioning
confidence: 99%